Overview of Oxidative Stress in Systemic Lupus Erythematosus - Ancuta Lupu; Gabriela Stoleriu; Alin Horatiu Nedelcu; Sara Nadeea Perju; Cristina Gavrilovici; Ginel Baciu; Cristina Maria Mihai; Tatiana Chisnoiu; Ionela Daniela Morariu; Ecaterina Grigore; Shwan Karwan Shawais; Delia Lidia Salaru; et al. (Antioxidants)
Systemic lupus erythematosus (SLE) is an autoimmune disease that is frequently diagnosed in female patients, caused by multiple interacting factors. It has a complex pathogenesis which can affect almost any organ, from the kidneys to the cardiovascular, pulmonary, neurological, osteoarticular, and hematological systems. The present narrative review seeks to elucidate the role of reactive oxygen species (ROS) in the pathogenesis of SLE. The central question guiding this study is to what extent these serum protein modifications correlate with disease activity and organ damage in SLE. It is characterized by the decreased apoptosis and increased necrosis of T cells and the NETosis of granulocytes. Given the impact of an SLE diagnosis on one’s life, this narrative review aims to evaluate the intricacies of oxidative stress and its relevance to the pathogenesis and treatment of the disease. Topics such as understanding processes of oxidative stress, their damaging pathways, oxidative stress biomarkers, and their role in the future assistance of clinical decisions will be discussed in the article. The accurate determination of biomarkers is taught to improve both the diagnosis and the management of the disease, while antioxidant therapy may open a new door for the treatment.